Silica-core perfluorinated polymer-shell composite nanoparticles for highly stable and efficient superhydrophobic surfaces. Issue 27 (26th June 2018) - Sohn, Eun-Ho; Kang, Hong Suk; Bom, Jeong-Cheol; Ha, Jong-Wook; Lee, Soo-Bok; Park, In Jun
Abstract : Self-assembly of newly synthesized silica-core/polyperfluoroalkyl acrylate-shell nanoparticles led to outstanding and stable superhydrophobic performance. Abstract : Silica-core/perfluorinated polymer-shell composite nanoparticles (NPs) were spray-coated onto an adhesive-coated surface to fabricate robust superhydrophobic surfaces. The spontaneous assembly of the NPs led to complex micro/nano dual-scale roughness and the epoxy adhesive layer in between the NPs and the substrate imparted high mechanical robustness to the surface against external damage.